Síntese de derivados de vitamina A utilizando lipase de Candida antartica imobilizada (Novozyme 435) - Siqueira, Ana Karine Pessoa Bastos (2007)
The main objective of this work was to synthesize vitamin A derivatives through an enzymatic route, as an alternative to chemistry route, more aggressive to the environment. The conversion of retinyl acetate into retinyl palmitate would result in a product with better market acceptance, since it is more stable than the ester used as substrate. Retinyl adipate synthesis, on the other hand, was studied in order to prepare a new vitamin A derivative. Both Vitamin A derivatives synthesized in this work were aiming the industrial production of cosmetics and foods. In this context, immobilized Candida antarctica type B lipase (Novozyme 435 with 571,48 UI/g ± 55,47) was used to catalyze the conversion of the substrates retinyl acetate, palmitic and adipic acids. In addition to these, molecular sieves was also added since the proposed reactions release water to the reaction media, which is not favorable to the desired ester synthesis. The retinyl palmitate synthesis was investigated by two factorial experimental design, using a total reactional volume of 2 mL. In the first, three variables were analyzed: rate between substrates, type of solvent and temperature. Retinyl acetate was kept in 0,1 mmol and palmitic acid varied between 0,1 and 0,5 mmol. Considering the acid partition coefficient, toluene and hexane were tested as solvents. The temperatures varied between 25 and 40°C, following a 23 factorial experimental design blocked with central points. In the second design, the influence of lipase (25, 50 e 75 mg) and molecular sieves (20, 50, 80 mg) amounts were studied using toluene or hexane as solvent, in accordance with a 32 factorial design. Experiments in a larger scale were performed not only to the produce retinyl palmitate, which was submitted to termic stability tests, but also to retinyl adipate, which is not commercially available and thereof it was recovered from the reactional media and identified by nuclear magnetic resonance. The statistical analysis of the results allowed the observation of significant effects. In the first planning, temperature and their interaction with the molar rate between the substrates were the significant variables. In the second, enzyme and the molecular sieves quadratic relation were significant in the yield of synthesis with toluene, but only the enzyme was significant when hexane was utilized. The retinyl palmitate separation was performed in silica C18 column and the purified sample was analyzed by differential scanning calorimetric – DS with a thermal event around 6.54ºC. In the case of retinyl adipate, no separation procedure was effective since there is a mixture formed between retinyl and diretinyl adipates.